Cogitum in the treatment of children with attention deficit hyperactivity disorder and subclinical epileptiform activity on the electroencephalogram - M. Yu. Bobylova (Русский журнал детской неврологии, 2023)
This article outlines the current concept of attention deficit hyperactivity disorder (ADHD) pathogenesis from the standpoint of neuroanatomy and impairments of neurotransmitter metabolism. N-acetyl-aspartate and N-acetyl-aspartyl-glutamate are crucial for ADHD development. These substances are involved in the interaction of neuronal networks, myelin maturation, and functioning of excitatory neurotransmitters (glutamatergic system). The active substance of Cogitum is a synthetic analogue of N-acetyl-aspartate. We analyzed the efficacy of Cogitum in 249 ADHD children with or without subclinical epileptiform activity on the electroencephalogram (children with cerebral palsy and epileptic seizures were excluded). Cogitum was most effective in improving attention, memory, and speech. None of the children had aggravation of epileptiform activity or developed epileptic seizures during treatment. Therefore, Cogitum is a safe drug to alleviate ADHD manifestations in children with subclinical epileptiform activity on the electroencephalogram.